OC-066 Toll like receptor 4 antagonist prevents acetaminophen induced acute liver failure in mice: a novel therapeutic strategy. (28th May 2012) - Shah, N; Dhar, D; Jover-Cobos, M; Davies, N A; Mookerjee, R P; Jalan, R
Abstract : Introduction: Without transplantation, about 40% of patients with acute liver failure (ALF) die. Its treatment is an unmet need. Unregulated inflammation plays an important role in the pathogenesis. Our hypothesis is that Toll like receptor 4 (TLR 4) is critical in the progression of inflammation in ALF. The aims of the study were to determine whether (1) administration of a novel TLR4 antagonist to an acetaminophen (APAP) model of ALF in mice would prevent liver injury. (2) TLR4 antagonist in ALF prolongs survival. (3) TLR4 KO are protected from the liver injury induced by APAP. Methods: Study 1 : 3 groups of CD1 mice were studied (n=6 in each group) Naive, APAP, 500 mg/kg single dose IP after overnight fasting). APAP+TLR4 antagonist, STM28 (Osaka, Japan); 20 μg IP, 1 h prior to administration of APAP and 6 h late). Study 2 : 3 groups of C57BL/6 mice were studied (n=6) in each group. Naive, APAP (500 mg/kg single dose IP), APAP+TLR4 antagonist; IAXO (Innaxon) 3 mg/kg IP, 1 h prior to administration of APAP and 6 h later. Study 3: C57BL/6 TLR4 KO were administered APAP 500 mg/kg and the respective naive controls were administered 500 mg/kg of saline. Biochemistry was measured using COBAS integra, Cytokines in plasma and tissue homogenate of liver, kidney and brain were measured using ELISA bead array. Brain water was measured using the dry-wet weight method. Results: Both the TLR4 antagonist's (STM28 and IAXO compound) reduced the plasma liver enzymes, ammonia and creatinine to the control level. The increase in the plasma TNF-α induced by APAP (45±3.2) was attenuated following TLR4 antagonist (20±2.3) (p<0.01). This was associated with a reduction in brain water (p<0.01). Both the TLR4 antagonists significantly reduced pericentral necrosis of the liver. Both these interventions showed an improvement in the survival as using the log rank test (p<0.02). TLR4 KO mice treated with APAP were protected from liver necrosis and had significantly better survival than wild type controls (p<0.002). Conclusion: These data provides evidence for an important of TLR4 in APAP induced ALF and provide the rationale for a clinical trial of this strategy in ALF. Competing interests: None declared.